Laminated pressurized elastic tube and its homogenization (Archives of Mechanics - Test, 1999)
In this paper the state of stress and deformation of a pressurized tube consisting of various elastic isotropic or transversely isotropic layers is evaluated. Especially a periodically laminated tube made of many thin layers is analysed by means of a homogenization process, and closed-form solutions are obtained. The results axe illustrated by means of a numerical example.